ADVANTAGES OF THE DRUG «ARMADYN» IN THE COMPLEX THERAPY OF CORONARY HEART DISEASE, STABLE ANGINA AND DYSCIRCULATORY ENCEPHALOPATHY - Ovcharenko, L.D.; Tsyganenko, I.V. (World of Medicine and Biology, 2016)
Development of recommendations about the choice of effective tactics in treatment the ischemic heart disease and table angina of tension, and encephalopathy, in particular, remains the topical problem in cardiology practice. Existent charts and principles of treatment eliminate possibility of the differently directed operating on a few pathological processes, especially they are not effective at simultaneous therapy on all levels of organization of organism. Nowadays the problem of effective treatment of the contiguous pathosiss predefined by the one disease stands sharply enough, in fact , in plenty various among drugs, which are necessary for treatment above-mentioned pathologies it is very difficult to avoid the polypharmacy ,even more to pick up the small amount of drugs ,which will give a positive effect in treatment.